Development and applicability of a multi-residue method for dyes, including new residue markers, to detect drug misuse in aquaculture. Issue 8 (3rd August 2021) - Touchais, Gaël; Bessiral, Mélaine; Hurtaud-Pessel, Dominique; Verdon, Eric; Dubreil, Estelle
ABSTRACT: A qualitative and quantitative liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed for the sensitive and exhaustive analysis of residues from triarylmethane dyes, triarylmethane-derivative dyes, phenothiazines, phenoxazines and xanthenes in aquaculture samples. For a wider and more robust detection of dye misuse on farms, other residue markers were also included the leuco forms of brilliant green, crystal violet and malachite green; one direct metabolite of Victoria pure blue BO and methylene blue and three bile acids, which are endogenous markers of the effects of dye contamination in fish. We optimised the extraction method by comparing several extraction solvents and sample solvents reported in the literature to have the best extraction efficiency. The residues were determined using a positive electrospray ionisation source. We assessed the parameters of this LC-MS/MS method by evaluating the matrix effects, identification and quantitative parameters according to the criteria stipulated in the European Commission Decision No. 2002/657/EC. A study on the applicability of the method was conducted on various aquaculture species and on a positive catfish.